Sarcopenia, a Neurogenic Syndrome? - Ping Kwan (Journal of Aging Research)
Sarcopenia is an aging-associated condition, which is currently characterized by the loss of muscle mass and muscle strength. However, there is no consensus regarding its characterization hitherto. As the world older adult population is on the rise, the impact of sarcopenia becomes greater. Due to the lack of effective treatments, sarcopenia is still a persisting problem among the global older adults and should not be overlooked. As a result, it is vital to investigate deeper into the mechanism underlying the pathogenesis of sarcopenia in order to develop more effective therapeutic interventions and to inscribe a more uniform characterization. The etiology of sarcopenia is currently found to be multifactorial, and most of the pharmacological researches are focused on the muscular factors in aging. Although the complete mechanism underlying the development of sarcopenia is still waiting to be elucidated, we propose in this article that the primary trigger of sarcopenia may be neurogenic in origin based on the intimate relationship between the nervous and muscular system, namely, the motor neuron and its underlying muscle fibers. Both of them are affected by the cellular environment and their physiological activity.